Effects of Dietary β-Carotene on the Gonadal Color, Pigmentation, and Regulation Mechanisms in Sea Urchin Strongylocentrotus Intermedius - Weixiao Di; Yinuo Zhang; Huinan Zuo; Haijing Liu; Lina Wang; Jun Ding; Yaqing Chang; Rantao Zuo (Fishes, 2025)
This study aims to clarify the dose–response relationship between dietary β-carotene levels and gonadal pigment deposition and regulation mechanisms related to the carotenoid synthesis of Strongylocentrotus intermedius based on a 60-day feeding trial and subsequent transcriptome analysis. Adult sea urchins (initial weight: 9.33 ± 0.21 g) of three cages were given one of the dry feeds with different doses of β-carotene (0 mg/kg, 150 mg/kg, 300 mg/kg) or fresh kelp (Saccharina japonica). The results indicated that the weight gain rate (WGR) of sea urchins increased with the addition of β-carotene, with that of the C300 group being markedly higher than that of the C0 group. The addition of β-carotene significantly improved the redness (a*) and yellowness (b*) values of the gonads, with sea urchins in the C300 group exhibiting closest gonad coloration to those in the kelp-fed group. Meanwhile, β-carotene and echinenone in the gonads of the C300 group showed the highest contents, reaching 1.96 μg/kg and 11.97 μg/kg, respectively. Several differential genes, enriched in the pathways of steroid biosynthesis, oxidative phosphorylation, and ubiquitination, were screened based on transcriptome analysis. Real-time PCR further demonstrated that β-carotene significantly upregulated the expression of cholesterol 25-hydroxylase (CH25H), NADH dehydrogenase subunit 1 (ND1), NADH dehydrogenase subunit 2 (ND2), and NADH dehydrogenase subunit 4 (ND4) while it downregulated the expression of 24-dehydrocholesterol reductase (DHCR24). These results showed that 300 mg/kg β-carotene significantly increased the WGR, redness, and yellowness values, as well as the contents of β-carotene and echinenone in the gonads of S. intermedius. On the one hand, dietary β-carotene increased NADH enzyme activity, which participates in echinenone synthesis by donating electrons for the transformation of β-carotene to echinenone synthesis. On the other hand, the addition of β-carotene inhibited cholesterol synthesis by increasing the expression of CH25H and decreasing the expression of DHCR24, which could in turn increase the fluidity and permeability of the cell membranes and the transport efficiency of β-carotene and echinenone from the digestive tract to the gonads. These results provided fundamental insights into the production of sea urchin gonads with market-favored colors.